THE EFFECTIVENESS OF GROUP BEHAVIORAL ACTIVATION THERAPY INTERVENTION FOR PATIENTS WITH DEPRESSION IN THANH HOA PROVINCE (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the effectiveness of group-based behavioral activation therapy at the community level for patients with depression in Thanh Hoa province.Subject and methods: A controlled intervention study was conducted among 242 participants aged 18-65 years with a PHQ-9 score of ≥ 10 in 6 communes of Quang Xuong district, Thanh Hoa province, from August 2024 to January 2025.Results: After 8 weeks of group behavioral activation intervention, the intervention group demonstrated significant improvements in depression (PHQ-9), psychological distress (BSRS-5), behavioral activation (BADS-SF), and resilience (BRCS), whereas the control group exhibited little or no change. Specifically, PHQ-9 scores decreased from 15.86 ± 3.68 to 7.00 ± 3.94 (p < 0.001), and BSRS-5 scores decreased from 13.77 ± 3.28 to 6.56 ± 3.94 (p < 0.001) in the intervention group. Meanwhile, BADS-SF scores increased from 24.22 ± 7.91 to 34.87 ± 6.92 (p < 0.001), and BRCS scores increased from 12.62 ± 4.03 to 15.81 ± 2.54 (p < 0.001). In contrast, the control group showed a tendency toward decline or non-significant changes.Conclusion: These findings confirm the effectiveness of group-based behavioral activation therapy in reducing depressive symptoms, enhancing behavioral activation, and improving resilience among patients with depression.
Keywords: Effectiveness, group intervention, behavioral activation, depression.